Risk factors for dropping out of neurosurgical residency programs: a survey study - Ottenhausen, Malte; Anetsberger, Stephanie; Kleffmann, Jens; Schuss, Patrick; Konczalla, Juergen; Krawagna, Maximilian; Burkhardt, Jan-Karl; Reitz, Matthias; Xu, Ran; Albers, Lucia; Ntoulias, Georgios; Meyer, Bernhard; et al. (World neurosurgery, 2018)
Background - Resident education has to adapt to a changing health care environment. Although aspects such as working hours and attrition rates have been studied in detail, data about the residents' perspective, especially in European countries, are underrepresented in the scientific literature. The aim of this study was to assess and report aspects of neurosurgical education in German-speaking countries and to identify risk factors for quitting or changing the neurosurgical residency program. - Methods - We conducted a nonanonymous online survey among neurosurgical residents in Germany, Austria, and Switzerland. Log-binomial regression models were calculated to further assess risk factors. - Results - Of 201 residents who responded to the survey, 37.3% (n = 75) dropped out of neurosurgical training programs, including 20 residents (10%) who ultimately quit neurosurgery and changed to another specialty. Only female gender (relative risk, 2.97; 95% confidence interval, 1.3-6.78) and starting residency in a city one studied or grew up in (2.38; 1.01-5.62) were significant risk factors. Residents who had close supervision at work (0.39; 0.17-0.89), who observed the residency program for >3 days before applying (0.54; 0.31-0.95), who had well-defined guidelines within the program (0.57; 0.35-0.92), and who were working in a university hospital (0.41; 0.26-0.64) were significantly less likely to quit or change their program. - Conclusions - The high attrition rate, especially among female residents, in Germany, Austria, and Switzerland should encourage program directors to specifically address the issues reported by this survey during interviews and to further improve their residency program accordingly.
Gesehen am 12.03.2020